THE ROLE OF PEDAGOGICAL TECHNOLOGIES IN PREPARING STUDENTS FOR COMMUNICATION (American Journal of Interdisciplinary Research and Development, 2023)
In this article, it is mentioned that the dialogue between the teacher and a particular student is important in preparing students for international communication, and the use of special technologies in preparing students for international communication and cooperation is also mentioned.